Chondroblastoma with secondary aneurysmal bone cyst in the anterior skull base - Ming Jie Wang, MD, PhD; Bing Zhou, MD (Interdisciplinary Neurosurgery, 2016)
Chondroblastoma with secondary aneurysmal bone cyst (ABC), especially in the anterior skull base, is an extremely rare condition. A 5-year-old boy presented with a large space-occupying lesion in the anterior skull base along with a left sided-epistaxis, proptosis and decreased vision. Radical excision of the lesion was performed by an endoscopic transnasal and transethmoidal approach. The patient recovered without any recurrence during a follow-up period of up to 28 months. Here, we review this rare case and discuss the clinical presentation and surgical treatment.